Effects of conservation tillage practices on ammonia emissions from Loess Plateau rain-fed winter wheat fields. (March 2015) - Yang, Yang; Zhou, Chunju; Li, Na; Han, Kun; Meng, Yuan; Tian, Xiaoxiao; Wang, Linquan
Abstract: Ammonia emissions from agricultural activities contribute to air pollution. For the rain-fed winter wheat system in the Loess Plateau there is a lack of information about ammonia emissions. Current study aimed to provide field data on ammonia emissions affected by conservation tillage practices and nitrogen applications. A two-year field experiment was conducted during 2011–2013 wheat growing seasons followed a split-plot design. Main plots consisted of one conventional tillage (CT, as the control) and five conservation tillage systems, i.e., stalk mulching (SM), film mulching (FM), ridge tillage (RT), ridge tillage with film mulch on the ridge (RTfm), and ridge tillage with film mulch on the ridge and stalk mulch in the furrow (RTfmsm); while subplots consisted of two nitrogen application rates, i.e., 0 and 180 kg N ha −1 . Ammonia emissions were measured using an acid trapping method with vented chambers. Results showed ammonia fluxes peaked during the first 10 days after fertilization. On average, nitrogen application increased ammonia emissions by 26.5% (1.31 kg N ha −1 ) compared with treatments without nitrogen application ( P  < 0.05). Ammonia fluxes were strongly dependent on soil ammonium, moisture, and temperature. Tillage systems had significant effects on ammonia emissions. On average, conservation tillage practices reduced ammonia emissions by 7.7% (0.46 kg N ha −1 ) compared with conventional tillage ( P  < 0.05), with FM most effective. Deep-band application of nitrogen fertilizer, stalk mulches, and film mulches were responsible for reductions in ammonia emissions from nitrogen fertilization in conservation tillage systems, thus they were recommended to reduce ammonia emissions from winter wheat production regions in the southern Loess Plateau. Highlights: Ammonia emissions were measured using a vented chamber method. Conservation tillage practices significantly reduce ammonia emissions. Deep-band application of nitrogen fertilizer reduces ammonia emissions. Film and stalk mulches can both reduce ammonia volatilization. Ammonia fluxes are strongly dependent on soil ammonium, moisture, and temperature.